Android Educational Game for Pancasila and Civic Education Learning - Haris Abdullah Fasha; Santi Ika Murpratiwi; Moh. Ali Albar; Ni Luh Putu Agetania (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2024)
In the digital era, traditional teaching methods often fail to engage students, especially in Pancasila and Civic Education. Lack of understanding of Pancasila values leads to declines in religious, humanitarian, and unity values among students, evidenced by frequent fights and bullying. To address this, an interactive Android-based game,